Cultivo da cana-de-açúcar e o uso do solo em áreas de preservação permanente - Oliveira, Francienne Gois [UNESP]; Seraphim, Odivaldo Jose [UNESP] (EIA Energy in Agriculture, 2011)
This study aimed to recognize the significant temporal changes in land use between 1984 and 2008 in Barra Bonita City/ SP and to analyze the conflicts of land use in permanent preservation areas (PPA) with reference to the Forest Code and Resolution N. 303/2002 of CONAMA. The GIS Idrisi Andes 5.0 – geographic information system was used and the images were processed by LANDSAT TM5. Maps of land use were obtained by Maxver supervised classification and showed that in 1984 the area occupied by sugar cane crop was about 10.50 ha (70%) in 1984 and 10.90 ha in 2008. In analysis of conflicts about land use in permanent preservation areas showed that in 24 years the sugar-cane crops increased 3.6% on PPA. The occupation was represented by adequate forest of 279.25 ha (31.5% of total) in 1984. In 2008, the sugar-cane crop was the biggest conflict in PPA occupying 357.9 ha and 11.4% corresponds to areas in preparation for use. This year, 59.5% of total PPA is at odds with environmental legislation.

Este trabalho teve como objetivo reconhecer as mudanças temporais significativas no uso do solo no município de Barra Bonita/SP, entre os anos de 1984 e 2008 e analisar os conflitos de uso da terra em áreas de preservação permanente tendo como referência legal o Código Florestal e a Resolução n. 303/2002, do CONAMA. Utilizou-se o sistema de informações geográficas – SIG Idrisi Andes 5.0 onde foram processadas as imagens do satélite LANDSAT TM5. Através da classificação supervisionada Maxver obtiveram-se os mapas de uso do solo que revelaram que em 1984 a área plantada de cana-de-açúcar era de aproximadamente 10.50 ha (70%) e 10.90 ha em 2008. Na análise dos conflitos de uso do solo em áreas de preservação permanente evidenciou-se que nos 24 anos avaliados a cana-de-açúcar aumentou 3,6% sobre a APP. As matas nativas cobriam a área de 279,25 ha (31,5% do total) no ano de 1984. No ano de 2008 verificou-se que a cultura da cana-de-açúcar representava o maior conflito na APP ocupando 357,9 ha da área e 11,4% corresponde ao solo em preparo. Neste ano, 59,5% do total da APP encontrava-se em desacordo com a legislação ambiental.
Sugar cane crop and land use in permanet preservation areas
Keywords: LANDSAT satellite; Environment; Use conflicts; Satélite LANDSAT; Ambiência; Conflitos de uso